Analisis Kritis Isu-isu Pendidikan Indonesia Dalam Kompetisi Di Kawasan ASEAN - Eriawaty Eriawaty (FKIP, Universitas Palangka Raya, 2020)
Equitable distribution of teachers in Indonesia still does not meet needs. The solutions offered are the recruitment and placement of new teachers, structuring the number and qualifications of existing teachers throughout Indonesia, increasing teacher competency through follow-up actions. Equitable education raises the formulation and issuance of Law No. 23 of 2014 concerning Regional Government. Implementation in the field experienced several obstacles. The issue of Indonesian as an ASEAN regional language led to the importation of Indonesian teachers from various ASEAN member countries. Teacher competencies and prospective teachers in Indonesia must be more prepared and improved, especially professional competence and pedagogical competence in dealing with this issue.